improving Pain mAnagement for childreN and young people attendeD by Ambulance (PANDA): protocol for a realist review. [version 3; peer review: 2 approved, 1 approved with reservations] - Paul Leighton; Georgette Eaton; Georgie Nicholls; Kacper Sumera; Marishona Ortega; Jessica Hodgson; Michael Baliousis; Aloysius Niroshan Siriwardena; Despina Laparidou; Bill Lord; Sarah Redsell; Gregory Adam Whitley; et al. (NIHR Open Research)
Background Each year in England, 450,000 children and young people (CYP) under 18 years of age are transported by ambulance to emergency departments. Approximately 20% of these suffer acute pain caused by illness or injury. Pain is a highly complex sensory and emotional experience. The intersection between acute pain, unwell CYP and the unpredictable pre-hospital environment is convoluted. Studies have shown that prehospital pain management in CYP is poor, with 61% of those suffering acute pain not achieving effective pain relief (abolition or reduction of pain score by 2 or more out of 10) when attended by ambulance. Consequences of poor acute pain management include altered pain perception, post-traumatic stress disorder and the development of chronic pain. This realist review will aim to understand how ambulance clinicians can provide improved prehospital acute pain management for CYP. Methods A realist review will be conducted in accordance with the Realist And Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) guidance. A five-stage approach will be adopted; 1) Developing an Initial Programme Theory (IPT): develop an IPT with key stakeholder input and evidence from informal searching; 2) Searching and screening: conduct a thorough search of relevant research databases and other literature sources and perform screening in duplicate; 3) Relevance and rigour assessment: assess documents for relevance and rigour in duplicate; 4) Extracting and organising data: code relevant data into conceptual “buckets” using qualitative data analysis software; and 5) Synthesis and Programme Theory (PT) refinement: utilise a realist logic of analysis to generate context-mechanism-outcome configurations (CMOCs) within and across conceptual “buckets”, test and refine the IPT into a realist PT. Conclusion The realist PT will enhance our understanding of what works best to improve acute prehospital pain management in CYP, which will then be tested and refined within a realist evaluation. Registration PROSPERO Registration: CRD42024505978